2000
DOI: 10.1590/s0100-879x2000000100001
|View full text |Cite
|
Sign up to set email alerts
|

Altered heart rate and blood pressure variability in mice lacking the Mas protooncogene

Abstract: Heart rate variability is a relevant predictor of cardiovascular risk in humans. A significant genetic influence on heart rate variability is suggested, although the genes involved are ill-defined. The Masprotooncogene encodes a G-protein-coupled receptor with seven transmembrane domains highly expressed in testis and brain. Since this receptor is supposed to interact with the signaling of angiotensin II, which is an important regulator of cardiovascular homeostasis, heart rate and blood pressure were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 32 publications
3
36
2
Order By: Relevance
“…Moreover, after sinus denervation, the percentage period of the negative correlation was markedly diminished in both groups. In addition, the baroreflex sensitivity determined by the spontaneous method in the WT mice agreed well with previously reported findings in mice by the drug-induced method (13) and spontaneous method (25). Thus the baroreflex sensitivity by the spontaneous method in the present study was reliable enough to clarify the difference in the sensitivity between the WT and KO mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, after sinus denervation, the percentage period of the negative correlation was markedly diminished in both groups. In addition, the baroreflex sensitivity determined by the spontaneous method in the WT mice agreed well with previously reported findings in mice by the drug-induced method (13) and spontaneous method (25). Thus the baroreflex sensitivity by the spontaneous method in the present study was reliable enough to clarify the difference in the sensitivity between the WT and KO mice.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the baroreflex sensitivity was evaluated from the pulse interval response to spontaneous change in arterial pressure in conscious cats (2), humans (6, 7), and anesthetized mice (25). It was determined that the sensitivity from the slope of the pulse intervals and the systolic pressure, based on the findings that changes in three or more consecutive pulse intervals in response to the preceding systolic arterial pressure were positively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the time to the peak of Ca 2ϩ current was statistically different when To further discard the possibility that the changes in collagen expression in cardiac function in vivo were secondary to increased BP, an additional group of animals at the same age of those used for echocardiograph measurements (6 months) were instrumented for acute BP recordings. As expected, 24,27 …”
Section: Massupporting
confidence: 86%
“…Accordingly, associated with the important deficit of systolic function, we have also found a significantly lower dimension of the left ventricle at the end of diastole and a decreased ϪdT/dt in isolated hearts of Mas Ϫ/Ϫ . Walther et al 27 have reported an increased BP variability and indirect evidence for an increased sympathetic tonus in male Mas Ϫ/Ϫ mice as compared with control mice (presumably C57BL/6 mice) using spectral analysis of BP data sampled at a relatively low frequency (250 Hz). Whether these changes contribute or are consequence or adaptative responses to the lower cardiac function remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…NEP gene inactivation actually caused a drop in blood pressure, 20 quite possibly because NEP is also key in the degradation of the vasodilatory bradykinin and natriuretic atrial natriuretic peptide (ANP). In contrast, mas inactivation had no apparent effect on mean systolic pressure but was reported to slightly decrease blood pressure variability in female, but not male, mice, 21 perhaps as a consequence of increased sympathetic tone. 22 Likewise, ACE2 inactivation had no detectable effect on blood pressure in animals up to 3 months of age.…”
Section: Physiological Correlates To Some Interesting Biochemistrymentioning
confidence: 79%